Role of R-spondin 2 in arterial lymphangiogenesis and atherosclerosis. Issue 6 (4th August 2020) - Singla, Bhupesh; Lin, Hui-Ping; Chen, Alex; Ahn, WonMo; Ghoshal, Pushpankur; Cherian-Shaw, Mary; White, Joseph; Stansfield, Brian K; Csányi, Gábor
Abstract: Aims: Impaired lymphatic drainage of the arterial wall results in intimal lipid accumulation and atherosclerosis. However, the mechanisms regulating lymphangiogenesis in atherosclerotic arteries are not well understood. Our studies identified elevated levels of matrix protein R-spondin 2 (RSPO2) in atherosclerotic arteries. In this study, we investigated the role of RSPO2 in lymphangiogenesis, arterial cholesterol efflux into lesion-draining lymph nodes (LNs) and development of atherosclerosis. Methods and results: The effect of RSPO2 on lymphangiogenesis was investigated using human lymphatic endothelial cells (LEC) in vitro and implanted Matrigel plugs in vivo . Cellular and molecular approaches, pharmacological agents, and siRNA silencing of RSPO2 receptor LGR4 were used to investigate RSPO2-mediated signalling in LEC. In vivo low-density lipoprotein (LDL) tracking and perivascular blockade of RSPO2–LGR4 signalling using LGR4-extracellular domain (ECD) pluronic gel in hypercholesterolemic mice were utilized to investigate the role of RSPO2 in arterial reverse cholesterol transport and atherosclerosis. Immunoblotting and imaging experiments demonstrated increased RSPO2 expression in human and mouse atherosclerotic arteries compared to non-atherosclerotic controls. RSPO2 treatment inhibited lymphangiogenesis both in vitro and in vivo . LGR4 silencing and inhibition of RSPO2–LGR4 signalling abrogated RSPO2-induced inhibition of lymphangiogenesis. Mechanistically, we found that RSPO2 suppresses PI3K-AKT-endothelial nitric oxide synthase (eNOS) signalling via LGR4 and inhibits activation of the canonical Wnt-β-catenin pathway. ApoE −/− mice treated with LGR4-ECD developed significantly less atherosclerosis compared with control treatment. Finally, increased arterial lymphatic vessel density and improved lymphatic drainage of fluorescently labelled LDL to deep cervical LNs were observed in LGR4-ECD-treated mice. Conclusion: These findings demonstrate that RSPO2 inhibits lymphangiogenesis via LGR4 and downstream impairment of AKT-eNOS-nitric oxide signalling. These results may also inform new therapeutic strategies to promote lymphangiogenesis and improve cholesterol efflux from atherosclerotic arteries.